2014
DOI: 10.5946/ce.2014.47.2.162
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Intractability to Endoscopic Hemostasis in the Treatment of Bleeding Gastroduodenal Peptic Ulcers in Japanese Patients

Abstract: Background/AimsDespite improvements in endoscopic hemostasis and pharmacological therapies, upper gastrointestinal (UGI) ulcers repeatedly bleed in 10% to 20% of patients, and those without early endoscopic reintervention or definitive surgery might be at a high risk for mortality. This study aimed to identify the risk factors for intractability to initial endoscopic hemostasis.MethodsWe analyzed intractability among 428 patients who underwent emergency endoscopy for bleeding UGI ulcers within 24 hours of arri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 27 publications
1
21
0
3
Order By: Relevance
“…Furthermore, unsuccessful endoscopic hemostasis was found to be an independent risk factor for rebleeding and was associated with increased 30-d mortality in patients with NVGIB[17,29,30]. These findings support the role of a primary effective endoscopic hemostasis.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, unsuccessful endoscopic hemostasis was found to be an independent risk factor for rebleeding and was associated with increased 30-d mortality in patients with NVGIB[17,29,30]. These findings support the role of a primary effective endoscopic hemostasis.…”
Section: Discussionmentioning
confidence: 77%
“…In addition the eradication of helicobacter pylori has decreased incidence rates of gastric and duodenal ulcers 1. Although the number of hospitalizations due to peptic ulcer disease has decreased during the last decades 2, in contrast to this nationwide trend, admission rates for gastric and duodenal ulcer hemorrhage and perforation in older patients even increased 3 and mortality rates remained essentially unchanged at 5 % to 8 % 4. This may in part be due to the increasing and intensive use of antithrombotic and/or anticoagulant medications for treatment of various cardiac, vascular or circulatory disorders in a consistently older population of patients with multiple morbidities 5 6.…”
Section: Introductionmentioning
confidence: 99%
“…[18] In the study by Ogasawara et al, [19] age ≥70 years, shock on admission, Hb <8.0 g/L, serum [14] that for a patient with American Society of Anesthesiologists (ASA) score 3 to 5, Hb <70 g/L, and endoscopy within 12 hours, the probability of finding high-risk NVUGIB would be 58%. In 2014, Giese et al [20] concluded that in patients with UGIB subject to after-hours endoscopy, a "high-risk" Rockall score permitted an estimation of the risk of death within 30 days, but not of rebleeding.…”
Section: Discussionmentioning
confidence: 99%